Microvascular Sprouting, Extension, and Creation of New Capillary Connections with Adaptation of the Neighboring Astrocytes in Adult Mouse Cortex under Chronic Hypoxia. Issue 2 (February 2014) - Masamoto, Kazuto; Takuwa, Hiroyuki; Seki, Chie; Taniguchi, Junko; Itoh, Yoshiaki; Tomita, Yutaka; Toriumi, Haruki; Unekawa, Miyuki; Kawaguchi, Hiroshi; Ito, Hiroshi; Suzuki, Norihiro; Kanno, Iwao
The present study aimed to determine the spatiotemporal dynamics of microvascular and astrocytic adaptation during hypoxia-induced cerebral angiogenesis. Adult C57BL/6J and Tie2-green fluorescent protein (GFP) mice with vascular endothelial cells expressing GFP were exposed to normobaric hypoxia for 3 weeks, whereas the three-dimensional microvessels and astrocytes were imaged repeatedly using two-photon microscopy. After 7 to14 days of hypoxia, a vessel sprout appeared from the capillaries with a bump-like head shape (mean diameter 14 μ m), and stagnant blood cells were seen inside the sprout. However, no detectable changes in the astrocyte morphology were observed for this early phase of the hypoxia adaptation. More than 50% of the sprouts emerged from capillaries 60 μ m away from the center penetrating arteries, which indicates that the capillary distant from the penetrating arteries is a favored site for sprouting. After 14 to 21 days of hypoxia, the sprouting vessels created a new connection with an existing capillary. In this phase, the shape of the new vessel and its blood flow were normalized, and the outside of the vessels were wrapped with numerous processes from the neighboring astrocytes. The findings indicate that hypoxia-induced cerebral angiogenesis provokes the adaptation of neighboring astrocytes, which may stabilize the blood–brain barrier in immature vessels.